2015
DOI: 10.1371/journal.pone.0137304
|View full text |Cite
|
Sign up to set email alerts
|

Marital Quality and Stress in Pregnancy Predict the Risk of Infectious Disease in the Offspring: The Norwegian Mother and Child Cohort Study

Abstract: ObjectivesThe aim of this study was to explore the degree to which couples’ relationship dissatisfaction and stressful life events during pregnancy predict the risk of infectious disease in the offspring during their first year of life.MethodsData were obtained from the Norwegian Mother and Child Cohort Study, conducted by the Norwegian Institute of Public Health. Pregnant women completed questionnaires in week 30 of pregnancy concerning the couples’ relationship satisfaction and stressful life events. In foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…In different parts of the world, the simultaneous occurrence of infections has been observed in infants who experience ELS, such as extreme poverty [28,29] or parental distress [30,31]. Further, children with severe infections in hospital often develop PTSD after discharge [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In different parts of the world, the simultaneous occurrence of infections has been observed in infants who experience ELS, such as extreme poverty [28,29] or parental distress [30,31]. Further, children with severe infections in hospital often develop PTSD after discharge [27].…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of clusters of extreme poverty (a type of ELS) and infectious diseases occurs worldwide [28,29]. Parental death, parental divorce [30], and maternal distress [31] influence the frequency and severity of infectious diseases during childhood. In the current study, our aim was to investigate the immediate effects of MS, together with an immune challenge (LPS), on astrocyte and microglial cell morphology, and its activation in the CA3 and hilus regions of the hippocampus, which are highly vulnerable to the effects of stress.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, the outcomes were assessed using registries. In the Norwegian Mother and Child Cohort Study, the researchers found a weak association between exposure to negative life events in pregnancy and infections in the first 12 months of infant's life . Finally, in a study based on a database of primary care medical records in the United Kingdom, children of mothers with perinatal depression had an increased risk of gastrointestinal and lower respiratory tract infections …”
Section: Discussionmentioning
confidence: 99%
“…Few previous studies also suggested a relationship between maternal mental health and common childhood infections …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation